Coronary Artery Fistula Presenting as a Rare Cause of Heart Failure - Pawan Suri; Kanika Kinra; Shyamli Sharma; Manmeet Pal Kaur (JK Science, 2021)
Coronary artery fistula (CAF) is an abnormal connection between one of the coronary arteries and a heart chamber or another blood vessel. The communication of the coronary artery could be with the lumen of a cardiac chamber (right ventricle - 41%, right atrium - 26%, left atrium - 5%, left ventricle - 3%), coronary sinus (7%), superior vena cava (SVC) (1%), pulmonary artery (17%) or the pulmonary vein. Here we present a rare case of CAF draining in SVC, which presented as heart failure, but on subsequent workup showed presence of fistula which was then surgically corrected successfully.